Pharmacokinetics and Repolarization Effects of Intravenous and Transdermal Granisetron - Mason, Jay W.; Selness, Daniel S.; Moon, Thomas E.; O'Mahony, Bridget; Donachie, Peter; Howell, Julian (Clinical cancer research, 2012)
Purpose: The need for greater clarity about the effects of 5-HT3 receptor antagonists on cardiac repolarization is apparent in the changing product labeling across this therapeutic class. This study assessed the repolarization effects of granisetron, a 5-HT3 receptor antagonist antiemetic, administered intravenously and by a granisetron transdermal system (GTDS). Experimental Design: In a parallel four-arm study, healthy subjects were randomized to receive intravenous granisetron, GTDS, placebo, or oral moxifloxacin (active control). The primary endpoint was difference in change from baseline in mean Fridericia-corrected QT interval (QTcF) between GTDS and placebo (ddQTcF) on days 3 and 5. Results: A total of 240 subjects were enrolled, 60 in each group. Adequate sensitivity for detection of QTc change was shown by a 5.75 ms lower bound of the 90% confidence interval (CI) for moxifloxacin versus placebo at 2 hours postdose on day 3. Day 3 ddQTcF values varied between 0.2 and 1.9 ms for GTDS (maximum upper bound of 90% CI, 6.88 ms), between −1.2 and 1.6 ms for i.v. granisetron (maximum upper bound of 90% CI, 5.86 ms), and between −3.4 and 4.7 ms for moxifloxacin (maximum upper bound of 90% CI, 13.45 ms). Day 5 findings were similar. Pharmacokinetic–ddQTcF modeling showed a minimally positive slope of 0.157 ms/(ng/mL), but a very low correlation (r = 0.090). Conclusion: GTDS was not associated with statistically or clinically significant effects on QTcF or other electrocardiographic variables. This study provides useful clarification on the effect of granisetron delivered by GTDS on cardiac repolarization. Clin Cancer Res; 18(10); 2913–21. ©2012 AACR.